I got better': narrative challenges to contemporary psychiatry - Wilk, Michelle, author; Cloud, Doug, advisor; Sloane, Sarah, committee member; Bone, Jennifer, committee member (Colorado State University. Libraries, 2016)
Mental illness is receiving significant amounts of attention, both via the media and via the medical system. Narratives are a way for people diagnosed with mental illnesses to share how they recovered from their illness. This study combines thematic narrative analysis as described by Arduser and a sample of narratives from the site I Got Better. Personal agency and rhetorical agency within the narratives are analyzed for a critical look at how much agency these narratives have. Their personal agency is analyzed through three recurring tropes: personal triumph, curating of relationships, and journey metaphors. The narrators' rhetorical agency is analyzed in light of the website's goals; even when they post on a site that states to be a collection of mental health recovery stories, they participate in a non-neutral forum. I Got Better builds an argument against the mental healthcare system, and in doing so imposes rhetorical limitations on the narrators. This analysis highlights how the narrators build agency for themselves and how they navigate the limitations and expectations of the website.